Penerapan Teknik Imajinasi Terbimbing melalui Media Virtual Reality pada Pasien Post Operasi dengan Masalah Keperawatan Nyeri Akut: Application of Guided Imagery Techniques through Virtual Reality Media in Post-Operative Patients with Acute Pain - Hondro, Wardiman Hondro; Wardah; M. Zul’ Irfan; Tison (Jurnal Keperawatan Berbudaya Sehat, 2025)
Postoperative pain is a significant health concern affecting approximately 35–65% of surgical patients. When left unmanaged, this type of pain can lead to complications such as bleeding, infection, respiratory distress, and a decline in overall quality of life. This study aimed to explore the application of guided imagery techniques using Virtual Reality (VR) as a non-pharmacological intervention to reduce pain intensity in postoperative patients. The research employed an experimental approach involving a single patient experiencing acute pain after surgery. The intervention was carried out on February 1, 2025, and lasted for 10 minutes. Findings indicated a significant reduction in pain intensity following the implementation of guided imagery through VR. Post-intervention evaluations showed that the patient met the outcome indicators outlined in the Indonesian Nursing Outcome Standards (SLKI), including decreased pain complaints, reduced grimacing, diminished protective behavior, decreased restlessness, less self-focus, as well as lower respiratory rate, pulse rate, and blood pressure. Based on these findings, it is recommended that nurses consider incorporating guided imagery using virtual reality as a complementary intervention in pain management to improve comfort and quality of life in postoperative care.